1992
DOI: 10.1051/agro:19921020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizers and arbuscular mycorrhizal fungi on the post-vitro growth of micropropagated strawberry

Abstract: Summary — A 5-wk factorial experiment was conducted to examine the effects of osmocote (18N:11P:10K; commercial controlled-release fertilizer), rock phosphate and 3 species of arbuscular mycorrhizal fungi on the growth of the strawberry cultivar Senga Sengana in a peat-sand-vermiculite substrate. Three Glomus species, G98 (probably G intraradices), G128 (an undescribed species) and G geosporum were compared. G98 and G128 significantly increased shoot dry weights compared with the non-mycorrhizal control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 10 publications
3
13
0
Order By: Relevance
“…Responses to inoculation are dependent both on the species of the micropropagated plant (Salamanca et al 1992) and AMF species (Williams et al 1992). The use of controlled release fertilisers has been investigated with a view to limiting the influence of high phosphate levels, often applied to plantlets during weaning, on the establishment of the symbiosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses to inoculation are dependent both on the species of the micropropagated plant (Salamanca et al 1992) and AMF species (Williams et al 1992). The use of controlled release fertilisers has been investigated with a view to limiting the influence of high phosphate levels, often applied to plantlets during weaning, on the establishment of the symbiosis.…”
Section: Introductionmentioning
confidence: 99%
“…The use of controlled release fertilisers has been investigated with a view to limiting the influence of high phosphate levels, often applied to plantlets during weaning, on the establishment of the symbiosis. These formulations have been successful with Williams et al 1992 demonstrating that the growth of AMF inoculated strawberries to which only 25 % of the minimum recommended rate of osmocote, a controlled release fertiliser, had been added had the same dry weight at harvest of non-inoculated plants receiving the full amount. Furthermore, Blal et al (1990) showed with micropropagated oil palm that in mycorrhizal plants the coefficient of fertiliser utilisation is increased.…”
Section: Introductionmentioning
confidence: 99%
“…CRF fertilizers have been tested on strawberries under field and greenhouse conditions (Albregts et al, 1990;Archbold et al, 1992;Williams et al, 1992). The use of CRFs has also been examined on blueberries (Hanson and Retamales, 1992;Naumann and Kruger, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal (AM) fungi have the effect of promoting host plant growth mainly by enhancing phosphorus uptake through symbiosis (Marschner and Dell, 1994). As for strawberry plants, growth enhancement through AM fungus inoculation was reported in several combinations of AM fungal species and strawberry cultivars (Robertson et al, 1988;Chavez and Ferrera, 1990;Niemi and Vestberg, 1992;Williams et al, 1992;Varma and Schuepp, 1994). Schenck and Smith (1982) and Haugen and Smith (1992) also reported that AM fungus-infected plants produced more dry weight of shoots and roots than non-inoculated ones under high soil temperature in soybean and mung bean, respectively.…”
Section: Introductionmentioning
confidence: 99%